The role of impairment of higher mental functions in suicidogenesis in the dementia caused by Alzheimer’s disease - Mudrenko, Iryna (Psychosomatic Medicine and General Practice, 2018)
Background. Dementia is the age-related disease. At the same time, the elderly age has one of the peaks in the number of suicides. Psychology of patients with demetia is characterized by the feeling of hopelessness, pessimism, awareness of own insolvency, dependence on others, that affects the risk of suicide. It is established that the highest risk of suicide in the early stages of dementia with the progression of cognitive deficit, the risk of suicide decreases. Aim. To study the role of impairment of higher mental functions (perception, reasoning, attention, memory, emotions, will, speech) in the formation of suicidal behaviour in patients with dementia in Alzheimer’s disease. Materials and methods. There were examined 75 patients with dementia in Alzheimer’s disease, 36 patients with a history of suicidal behavior composed the main group, and 39 patients without the signs of suicidal behavior composed control group. The study was carried out using clinical-anamnestic, psychopathological methods and mathematical statistical methods. Results. The high risk of suicide in dementia caused by Alzheimer’s disease is combined with the inhibition of thinking, the delusional ideas of self-blame and self-effacement (p ≤ 0.05); depressed mood, inner agitation, anxiety, feeling of despair, hopelessness, guilt, melancholia, apathy (p ≤ 0.05); effector-volitional disorders in the form of hypobulia, hypokinesia, hypomimia, decreased libido (p ≤ 0.05); speech disturbance in the form of bradylalia p ≤ 0.05; greater exhaustion and decreased attention (p ≤ 0.05). On the contrary, the following peculiarities of higher mental functions, namely thought disorder are referred to the anti-risk factors of suicide in dementia caused by Alzheimer’s disease: the delusional ideas of relation and damage (p ≤ 0.05); emotions: the feeling of fear (p ≤ 0.05); effector-volitional sphere: parabulia and hyperkinesia (p ≤ 0.05). Conclusion. On the basis of clinical and psychopathological study of patients with dementia in Alzheimer’s disease, the specific impairment of higher mental functions and emotional-volitional spheres reasoning, memory, attention, perception, speech, emotions) are identified associated with high risk of suicide.